The national and provincial state of Santa Fe and their capacities to promote the industrial sector: a theoretical-analytical proposal and an empirical study for the years 2020-2023. (Desarrollo, Estado y Espacio, 2025)
This paper elaborates a theoretical framework to examine the configuration of the state and its capacities to drive the development of the industrial sector within the contemporary capitalist economy. The framework results from bringing into dialogue two perspectives on the state: the state-centric approach and the strategic-relational-spatial approach. Based on this contribution, the article analyzes the Argentine national state and the provincial state of Santa Fe during the period 2020–2023. The main findings of the empirical study reflect the limitations of the Argentine state, in its multiscalar organization, to effectively promote the industrial sector and foster development.
Keywords: State; state capacities; development; Santa Fe; Argentina